The role of benralizumab in eosinophilic immune dysfunctions: a case report-based literature review - Gomes, Margarida (2023)
In the past years, the knowledge of eosinophils playing a primary pathophysiologic role in several associated conditions has led to the development of biologics targeting therapies aiming at normalizing the immune response, reducing chronic inflammation, and preventing tissue damage. To better illustrate the potential relationship between different eosinophilic immune dysfunctions and the effects of biological therapies in this scenario, here, we present a case of a 63-year-old male first referred to our department in 2018 with a diagnosis of asthma, polyposis, and rhinosinusitis and presenting a suspicion of nonsteroidal anti-inflammatory drugs' allergy. He also had a past medical history of eosinophilic gastroenteritis/duodenitis (eosinophilia counts >50 cells/high-power field HPF). The use of multiple courses of corticosteroid therapy failed to completely control these conditions. In October 2019, after starting benralizumab (an antibody directed against the alpha chain of the IL-5 cytokine receptor) as an add-on treatment for severe eosinophilic asthma, important clinical improvements were reported both in the respiratory (no asthma exacerbations) and gastrointestinal systems (eosinophilia count 0 cells/HPF). The patient's quality of life also increased. Since June 2020, systemic corticosteroid therapy was reduced without worsening gastrointestinal symptoms or eosinophilic inflammation. This case warns of the importance of early recognition and appropriate individualized treatment of eosinophilic immune dysfunctions and suggests the conduction of further larger studies on the use of benralizumab in gastrointestinal syndromes aiming at better understanding its relying mechanisms of action in the intestinal mucosa.